Problematika Legislasi dalam Sistem Pemerintahan Presidensial Multipartai - Ach. Faidi (Fakultas Syariah IAIN Madura, 2021)
This research raises the issue of legislation in the multi-party presidential government system in Indonesia after the amendment to the 1945 Constitution. In order to make this research more focused, the researcher proposes two main questions, namely; How exactly are the legislative problems that occur in a multi-party presidential government system? Likewise, how are the efforts to resolve the legislative problems in a multi-party presidential government system?. To answer these two problems, the researcher uses several approaches in this normative research. Among these approaches are the statutory approach, the conceptual approach, the historical approach and the case approach. Based on the results of the discussion in this study, the researcher concludes two main conclusions related to the problematics of legislation in the multi-party presidential government system in Indonesia after the amendments to the 1945 Constitution. namely, the weakening of the president's power in terms of legislation due to the increasing influence of the DPR's power in the legislative process, even though the president has double role. Furthermore, the legislative problem that occurs in the multi-party presidential system of government in post-amendment Indonesia is the waning spirit of upholding the principle of checks and balances in the formation of legislation.